Evaluating the change in Streptococcus mutans in plaque around orthodontic brackets using fluoride toothpaste, probiotic curd, and recaldent - A comparative in-vivo study - Mueez Bashir, Shedam; Ajit, Kalia; Hegde, Ashwith; Nasim, Mirdehghan; Burhanuddin Kutub, Malpurwala (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2019)
Introduction: Enamel demineralization is still a problem associated with orthodontic treatment, leading to the formation of white spot lesions;this is a grave concern to orthodontists and patients. Various methods are now employed to reduce the incidences of demineralization.Aim: To evaluate and compare the effects of Fluoride toothpaste, Probiotic curd, and Recaldent on Streptococcus mutans colonies inplaque around orthodontic brackets in different groups of patients. Further, the three agents were compared and assessed for regular useby orthodontic patients for reduction of decalcification.Materials and methods: This study consisted of 60 randomly selected patients having orthodontic treatment in the Department oforthodontics and dentofacial orthopaedics. The study protocol was approved by the institutional Ethics committee of MCE Society,Azam Campus, Pune. Group A: The patients were given fluoride containing toothpaste (ParodontaxTM Daily Fluoride toothpasteGlaxoSmithKline). Group B: The patients were asked to brush twice daily with recaldent containing tooth mousse (Dentsply ToothMousse- GC). Group C: Patients were given probiotic curd(Nestle Acti Plus). Samples were collected twice, once initially, seven days afterbonding at the start of the study and secondly, after 30 days. After DNA extraction PCR analysis was done to evaluate the colonies ofS. mutans as colony forming units per milliliter (CFU/ml) in the plaque specimens. RealPlex software programme was used to plot theresults of the colonies detected in the sample.Results: Streptococcus mutans colonies around the brackets after 30 days post use of Fluoride toothpaste, probiotic curd and Recaldentwas reduced by 44.5 %, 0.86 % and 41.8% respectively.Conclusion: The regular use of fluoride toothpaste and Recaldent will help in reducing decalcification during orthodontic treatment.Further research is needed to establish the advantages of probiotic curd in reducing white spot lesions.